KEEFEKTIFAN KELOMPOK TANI SEBAGAI MEDIA PENYULUHAN DALAM PENERAPAN TEKNOLOGI BUDIDAYA PADI SAWAH DI KECAMATAN BANGUNTAPAN KABUPATEN BANTUL - , NANDANG WIDARMINTO; , Ir. Roso Witjaksono, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research was purposed to find out the effectivity rate of farmers group as extension media on the application of paddy cultivation and the influencing factors, and also to find out the influence of effectivity of farmers group as extension media toward application paddy cultivation in Banguntapan sub-district, Bantul District. The sample was taken by using purposive methods, by considering that of village has an active farmers group on extension activity, namely Wirokerten village, Potorono village and Baturetno village. It took one active farmer group from each village by using purposive method, namely Ngudi Makmur Farmers Group (Potorono village), Ngudi Makmur Farmers Group (Wirokerten village) and Retno Tani Rukun Farmers Group (Baturetno village). From each group farmer, was selected 20 farmers as sample by using simple random sampling, so there were 60 farmers as sample. Data analysis has been done by using proportion test, multiple linear regression test and simple linear regression test. The result showed that effectivity rate of farmers group as extension media on application paddy cultivation technology can be categorized as high. The influencing on factor that effectivity of farmers group as extension media on application paddy cultivation technology were the role of extension worker and the presence of extension worker to farmers group